Anticholinergic Accumulation: A Slumbering Interaction between Drugs and Food Supplements. Issue 6 (24th July 2015) - Vrolijk, Misha F.; Opperhuizen, Antoon; Jansen, Eugène H. J. M.; Bast, Aalt; Haenen, Guido R. M. M.
Abstract: Many compounds display anticholinergic effects which might give rise to cognitive impairment and even delirium. These side effects are caused by their ability to bind to muscarinic receptors in our brain. Especially with combination of compounds, these serious effects are seen. This phenomenon, known as anticholinergic accumulation, is especially seen in the elderly. A classification of drugs for anticholinergic side effects has been made based on clinical observations, the ACB score. Here, we aimed to substantiate this classification by comparing the affinity of numerous drugs for the muscarinic receptors to the ACB score. Additionally, a number of supplements were screened. The affinity of the compounds was determined by their ability to displace the radioligand [ 3 H]pirenzepine of the muscarinic receptor induced by these compounds. Our results show that the affinity of a compound for the muscarinic receptors correlated with its ACB score. Also food supplements appeared to bind to these muscarinic receptors. Moreover, several drug–drug, supplement–supplement and supplement–drug combinations had an affinity that is higher than the affinity of single compounds. This explains the phenomenon of anticholinergic accumulation. In conclusion, care should be taken to drug–drug and supplement–drug combinations with respect to anticholinergic accumulation.